THE VITAL ROLE OF ACCOUNTING IN OPTIMISING MARKETING COMMUNICATION STRATEGIES - Teguh Prakoso; Desi Yuniarti (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
The vital role of accounting in optimising marketing communication strategies refers to the integration of accounting principles and practices into the planning, execution and evaluation of marketing campaigns. This concept involves using financial data, cost-benefit analyses, and performance metrics to improve the effectiveness and efficiency of marketing efforts. By combining accounting expertise with marketing creativity, companies can make more informed decisions, allocate resources more appropriately, accurately measure return on investment, and adjust strategies based on measurable results. This integrated approach not only improves the performance of individual campaigns but also contributes to the overall success and sustainability of the business in the long run. The review in this study used the literature method. The main findings show that the application of financial metrics in marketing planning and evaluation results in higher return on investment and better risk management. In addition, the integration of accounting in marketing communication strategies increases transparency and accountability, which are important for building stakeholder trust and regulatory compliance.